The role of specialist inpatient rehabilitation services for people with intellectual disability, autism and mental health, behavioural or forensic needs. Issue 5 (21st August 2019) - Odiyoor, Mahesh; Tromans, Samuel Joseph; Alexander, Regi T.; Akbari, Srinaveen; Bell, Gill; Bering, Sandy; Jaydeokar, Sujeet; Shetty, Amrith
Abstract : Purpose: The purpose of this paper is to provide a professional consensus position with regard to the provision of specialist inpatient rehabilitation services for people with intellectual disability (ID), autism and mental health, behavioural or forensic needs in the UK. Design/methodology/approach: The concept of rehabilitation is discussed, as well as the functions and goals of specialist inpatient rehabilitation services with regard to the aforementioned contexts. Current use of rehabilitation beds is considered, both on a regional and national scale, as well as various outcome measures, including effectiveness, patient safety and patient experience. Findings: There is a clear need for specialist inpatient rehabilitation services, though historically there have been instances of inappropriate admissions, as well as lengthy inpatient stays that could have been significantly reduced with the right type of community support package. Such services should be subjected to rigorous measurement of outcome measures, to determine that patients within such services are receiving a consistently high standard of care. Additionally, amendments to current legal frameworks should be considered, with a view to accommodating for individuals with capacity who require continuous community-based supervision. Originality/value: To the best of the author's knowledge, this is the first article detailing a professional consensus position for specialist inpatient rehabilitation services for people with ID, autism and mental health, behavioural or forensic needs.